2017
DOI: 10.1186/s13045-017-0434-y
|View full text |Cite
|
Sign up to set email alerts
|

Mutational profiling of acute lymphoblastic leukemia with testicular relapse

Abstract: Relapsed acute lymphoblastic leukemia (ALL) is the leading cause of deaths of childhood cancer. Although relapse usually happens in the bone marrow, extramedullary relapse occasionally occurs including either the central nervous system or testis (<1–2%). We selected two pediatric ALL patients who experienced testicular relapse and interrogated their leukemic cells with exome sequencing. The sequencing results and clonality analyses suggest that relapse of patient D483 directly evolved from the leukemic clone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Despite great advances, relapsed and refractory B cell acute lymphoblastic leukemia (B-ALL) shows unfavorable prognosis, especially for adult patients [ 1 , 2 ]. Although newly diagnosed ALL patients co-occurring with extramedullary involvement are rare, ALL with extramedullary tissues (EM-ALL) occurs in about 15 to 20% of all the relapse patients [ 3 ]. The central nervous system (CNS) is a favorable site for ALL relapse, accounting for two thirds of extramedullary relapse [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite great advances, relapsed and refractory B cell acute lymphoblastic leukemia (B-ALL) shows unfavorable prognosis, especially for adult patients [ 1 , 2 ]. Although newly diagnosed ALL patients co-occurring with extramedullary involvement are rare, ALL with extramedullary tissues (EM-ALL) occurs in about 15 to 20% of all the relapse patients [ 3 ]. The central nervous system (CNS) is a favorable site for ALL relapse, accounting for two thirds of extramedullary relapse [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, incorporation with TLR2 domain improves expansion of CAR-T cells and potentiates the killing capacity of CAR T cells against CD19 + leukemic cells [ 12 ]. Actually, the leukemia cells with potent abilities for cell migration, proliferation, adhesion, and protease activity facilitated themselves extramedullary infiltration [ 3 , 4 ]. In this context, it is highly warranted to find tumor-specific T cells with enhanced activity against the leukemic cells of high affinity for the extramedullary relapse.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, BCR-ABL1 compound mutations and other ABL1 tyrosine kinase inhibitors (TKIs) can also confer high-level resistance to imatinib [24]. Several research groups have also screened relapse-related gene mutations, including RAS and CREBBP/NT5C2 mutations in ALL patients [25, 26]. However, the correlation between clonal evolution and FISH signal patterns has not been well established in BCR-ABL1 positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…35 In another study, mutations in CREBBP and KRAS were also implicated in the mechanism through which the disease returns; aberrations in CREBBP and KRAS were found in a leukemic clone at diagnosis that also persisted at relapse, indicating that a clone harboring such abnormalities were responsible for the disease recurrence. 36 Another piece of evidence of the key role of impaired drug-responsive genes in the therapy failure of pediatric B-ALL came from a study that reported a significant association of deleted genes known to function in glucocorticoid signaling, such as BTG1 (B-cell translocation protein 1), NR3C1 (glucocorticoid receptor) and TBL1XR1 (transducin beta-like 1X-linked receptor 1), with relapsed cases of pediatric B-ALL. 27 Characterization of genome-wide copy number alterations (CANs) in matched diagnosis and relapse samples from 20 patients revealed that the relapse samples were associated with deletions of genes linked to the development and differentiation of B-cells.…”
Section: Omics-based Insights Into Therapy Failure In Patients With Pmentioning
confidence: 99%